Does Jesus really love me? : a gay Christian's pilgrimage in search of God in America - Chu, Jeff (Harper, 2013)
A writer for Time magazine, after coming out to his parents as a gay man, documents his personal journey, from Brooklyn to California, to discover the God forbidden to him because of his sexuality and understand what the diverse followers of Christ believe about homosexuality. An intellectual, emotional, and spiritual pilgrimage that reveals a nation in crisis.